2000
DOI: 10.1021/bi0020630
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Gene Expression Inside Cells by Peptide Nucleic Acids:  Effect of mRNA Target Sequence, Mismatched Bases, and PNA Length

Abstract: Genome sequencing has revealed thousands of novel genes, placing renewed emphasis on chemical approaches for controlling gene expression. Antisense oligomers designed directly from the information generated by sequencing are one option for achieving this control. Here we explore the rules governing the inhibition of gene expression by peptide nucleic acids (PNAs) inside cells. PNAs are a DNA/RNA mimic in which the phosphate deoxyribose backbone has been replaced by uncharged linkages. Binding to complementary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
98
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 149 publications
(106 citation statements)
references
References 43 publications
7
98
0
1
Order By: Relevance
“…It was also reported that intron -exon splice junctions were very sensitive targets for PNA antisense probes because correct mRNA splicing can be altered by PNA binding. 15 The good stability of PNA oligomers, their strong binding efficiency and their lack of toxicity at even relatively high concentrations suggests that PNAs could constitute highly efficient compounds for effective antisense/antigene application. However, despite the initial 18 Another strategy adapted to improve the in vivo delivery of PNA can be their incorporation into liposomes.…”
Section: Antisense and Antigene Applicationsmentioning
confidence: 99%
“…It was also reported that intron -exon splice junctions were very sensitive targets for PNA antisense probes because correct mRNA splicing can be altered by PNA binding. 15 The good stability of PNA oligomers, their strong binding efficiency and their lack of toxicity at even relatively high concentrations suggests that PNAs could constitute highly efficient compounds for effective antisense/antigene application. However, despite the initial 18 Another strategy adapted to improve the in vivo delivery of PNA can be their incorporation into liposomes.…”
Section: Antisense and Antigene Applicationsmentioning
confidence: 99%
“…PNA has been reported to resist nuclease and protease degradation (29) and can enhance acid specificity and inhibit mRNA expression (30,31). Furthermore, these modifications can increase the flexibility and binding affinities of PNA for its complementary single-stranded PNA, exceeding that of comparable DNAs (28).…”
mentioning
confidence: 99%
“…Relative to DNA and RNA oligonucleotides, these modifications increase the flexibility and binding affinity of PNA to complementary DNA or mRNA. PNAs have been shown to enhance nucleic acid specificity and inhibit protein expression (22,23). However, the major disadvantage of PNA is its poor cellular uptake.…”
mentioning
confidence: 99%